Peripheral levels of superoxide dismutase and glutathione peroxidase in youths in ultra-high risk for psychosis: a pilot study. (17th December 2017) - Zeni-Graiff, Maiara; Rios, Adiel C.; Maurya, Pawan K.; Rizzo, Lucas B.; Sethi, Sumit; Yamagata, Ana S.; Mansur, Rodrigo B.; Pan, Pedro M.; Asevedo, Elson; Cunha, Graccielle R.; Zugman, André; Bressan, Rodrigo A.; et al.
Abstract : Introduction: Oxidative stress has been documented in chronic schizophrenia and in the first episode of psychosis, but there are very little data on oxidative stress prior to the disease onset. Objective: This work aimed to compare serum levels of superoxide dismutase (SOD) and glutathione peroxidase (GPx) in young individuals at ultra-high risk (UHR) of developing psychosis with a comparison healthy control group (HC). Methods: Thirteen UHR subjects and 29 age- and sex-matched healthy controls (HC) were enrolled in this study. Clinical assessment included the Comprehensive Assessment of At-Risk Mental States (CAARMS), the Semi-Structured Clinical Interview for DSM-IV Axis-I (SCID-I) or the Kiddie-SADS-Present and Lifetime Version (K-SADS-PL), and the Global Assessment of Functioning (GAF) scale. Activities of SOD and GPx were measured in serum by the spectrophotometric method using enzyme-linked immunosorbent assay kits. Results: After adjusting for age and years of education, there was a significant lower activity of SOD and lower GPX activity in the UHR group compared to the healthy control group (rate ratio [RR]=0.330, 95% CI 0.187; 0.584, p<0.001 and RR=0.509, 95% CI 0.323; 0.803, p=0.004, respectively). There were also positive correlations between GAF functioning scores and GPx and SOD activities. Conclusion: Our results suggest that oxidative imbalances could be present prior to the onset of full-blown psychosis, including in at-risk stages. Future studies should replicate and expand these results.